Dynamics of Intersexual Dominance and Adult Sex- Ratio in Wild Vervet Monkeys - Hemelrijk, Charlotte Korinna; Wubs, Matthias; Gort, Gerrit; Botting, Jennifer; van de Waal, Erica (Frontiers in Psychology, 2020)
Intersexual dominance relations are important for female mammals, because of their consequences for accessing food and for the degree of sexual control females experience from males. Female mammals are usually considered to rank below males in the dominance hierarchy, because of their typical physical inferiority. Yet, in some groups or species, females are nonetheless dominant over males. Intersexual dominance, therefore, also depends on traits other than sexual dimorphism, such as social support, social exchange, group adult sex-ratio and the widespread self-reinforcing effects of winning and losing fights, the ‘winner-loser effect’. The importance of sex-ratio and the winner-loser effect remains poorly understood. A theoretical model, DomWorld, predicts that in groups with a higher proportion of males, females are dominant over more males when aggression is fierce (not mild). The model is based on a small number of general processes in mammals, such as grouping, aggression, the winner-loser effect, the initially greater fighting capacity of males than females, and sex ratio. We expect its predictions to be general and suggest they be examined in a great number of taxa and species. Here, we test these predictions in four groups of wild vervet monkeys (Chlorocebus pygerythrus) in Mawana game reserve in Africa, using seven years of data. We confirm that the proportion of males in the group is associated with greater dominance of females over males; a result that remains when combining these data with those of two other sites (Amboseli and Samara). We additionally confirm that in groups with a higher fraction of males there is a relatively higher a) proportion of fights of males with other males, and b) proportion of fights won by females against males from the fights of females with any adults. We reject alternative hypotheses that more dominance of females over males could be attributed to females receiving more coalitions from males or females, or females receiving lowered male aggression in exchange for sexual access (the docile male hypothesis). We conclude that female dominance relative to males is dynamic and that future empirical studies of inter-sexual dominance will benefit by considering the adult sex-ratio of groups.